Diversity of Arthropods and Parasitic Nematodes Population in Intercropping Patterns of Robusta Coffee - Dwi Suci Rahayu; Soekadar Wiryadiputra (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Shade plants affect the microclimates around the plants which directly affect the population of arthropods, especially insects. Therefore, this research was needed to analyze the diversity and role composition of insects in Robusta coffee plantations based on different intensity of shade plants. Samplings of insects and parasitic nematodes were conducted in intercropping patterns of Robusta coffee namely mixed intercropping patterns, coffee-pepper intercropping patterns and coffee-banana intercropping patterns. In each intercropping pattern of Robusta coffee, samplings were conducted as much as ten plants using random sampling. Data analysis was done by calculating the Shannon-Wiener diversity index (H') and evenness index (E). The results showed that diversity index in all Robusta coffee intercropping patterns were < 3, indicating that the diversity of insects in all intercropping patterns was relatively. Insect diversity in coffee-pepper inter- cropping pattern is found higher than the one in either mixed intercropping pattern or coffee-banana intercropping patterns. Out of those intercropping patterns, insects from Formicidae family of Hymenoptera order was found to be the most dominant insects. The composition of insects in all of those three intercropping patterns has been mainly dominated by insects from the family of Formicidae and Hymenoptera order since they are natural enemy insects. Pratylenchus coffeaehas been confirmed as the most dominant nematode species in the three Robusta coffee intercropping pattern. P. coffeae had the highest population average of 3279 in coffee-pepper intercropping pattern.